Synthesis and optimization studies of Fructose palmitate - Azalina, Mohamed Nasir
Fructose palmitate (sugar ester) is a relatively new class of nonionic surfactants. Their excellent biodegradability and low toxicity surfactant as well as effectiveness at extreme temperature, pH and salinity show their increasing importance in numerous areas of application. For a long time, large scale production of sugar ester was dominated by conventional chemical processing. However, the conventional chemical process leaves out bad impact to the human and environment. Compared to the enzymatic synthesis, this process offers a safer and easier alternative. In the present work, sugar ester production was developed by a novel and effective enzymatic method which can reduce the advantages of conventional chemical process. Direct unprotected sugar and non activated fatty acid were used as a starting material. Combination of supersaturated sugar solution under anhydrous condition and stepwise addition of molecular sieve as water absorbent agent during the reaction were found to be a suitable method in increasing the reaction rate and fatty acid conversion. In this method, influences of several parameters were investigated as a screening to the optimization process. Results from screening were used to optimize and analyze fructose palmitate (sugar ester) esterification using a response surface methodology (RSM) based on central composite design (CCD). The 98.58 ± 0.52% of optimum fatty acid conversion was determined by 11.92% (w/w of substrates) immobilized enzyme loading, 0.50M fatty acid concentration, 10.0h reaction time and 53.67oC of reaction temperature. The reusability of the immobilized enzyme was shown good conversion, were greater than 88% of fatty acid conversion after 10th reaction cycles without additional treatment of the immobilized enzyme.